Apolipoprotein C-II Mimetic Peptide Promotes the Plasma Clearance of Triglyceride-Rich Lipid Emulsion and the Incorporation of Fatty Acids into Peripheral Tissues of Mice. (3rd February 2019) - Komatsu, Tomohiro; Sakurai, Toshihiro; Wolska, Anna; Amar, Marcelo J.; Sakurai, Akiko; Vaisman, Boris L.; Sviridov, Denis; Demosky, Stephen; Pryor, Milton; Ikewaki, Katsunori; Remaley, Alan T.
Abstract : Aim . Plasma apolipoprotein C-II (apoC-II) activates lipoprotein lipase (LPL) and thus lowers plasma triglycerides (TG). We previously reported that a human apoC-II mimetic peptide (C-II-a) decreased plasma TG in apoC-II mutant mice, as well as in apoE-knockout mice. Because it is unknown what tissues take up free fatty acids (FFAs) released from TG after C-II-a peptide administration, we investigated in mice TG plasma clearance and tissue incorporation, using 3 H-triolein as a tracer, with and without C-II-a treatment. Methods and Results . Intralipid® fat emulsion was labeled with 3 H-triolein and then mixed with or without C-II-a. Addition of the peptide did not alter mean particle size of the lipid emulsion particles (298 nm) but accelerated their plasma clearance. After intravenous injection into C57BL/6N mice, the plasma half-life of the 3 H-triolein for control and C-II-a treated emulsions was 18.3 ± 2.2 min and 14.8 ± 0.1 min, respectively. In apoC-II mutant mice, the plasma half-life of 3 H-triolein for injected control and C-II-a treated emulsions was 30.1 ± 0.1 min and 14.8 ± 0.1 min, respectively. C57BL/6N and apoC-II mutant mice at 120 minutes after the injection showed increased tissue incorporation of radioactivity in white adipose tissue when C-II-a treated emulsion was used. Higher radiolabeled uptake of lipids from C-II-a treated emulsion was also observed in the skeletal muscle of C57BL/6N mice only. In case of apoC-II mutant mice, decreased uptake of radioactive lipids was observed in the liver and kidney after addition of C-II-a to the lipid emulsion. Conclusions . C-II-a peptide promotes the plasma clearance of TG-rich lipid emulsions in wild type and apoC-II mutant mice and promotes the incorporation of fatty acids from TG in the lipid emulsions into specific peripheral tissues.